PROFILE OF COMMUNITY ACQUIRED PNEUMONIA IN CHILDREN AT SOETOMO HOSPITAL SURABAYA IN 00â00 - Setyoningrum, Retno Asih (Institute of Topical Disease, 2011)
Background: Community Acquired Pneumonia (CAP) is one of the most important health problem affecting children all over the world. Clinical findings, laboratory and radiological examination of CAP may largely vary from mild to severe. Objective: To report profile of CAP in children hospitalized at Soetomo Hospital Surabaya in 2007â2008 Methods: This research was a retrospective study. Data of children with primary diagnosis of CAP in 2007â2008 were obtained from medical records of the Department of Child Health Soetomo Hospital Surabaya. The diagnosis CAP was based on WHO criteria (pneumonia clinical syndrome). The clinical features of illness, laboratory and radiological examination were recorded and presented descriptively. Results: During the study period, 438 patients were diagnosed as CAP. More than half (83.4%) patients aged 3 monthsâ 3 year. Beside cough and tachypnea, most common symptom and signs were chest indrawing (76.2%) and fever (23.8%). Leucocytosis (39.6%). Bacteria was found in 8.2%. Accompanying diseases (i.e congenital heart disease, neurological and gastroenterological disorders) were found in 36.4%. One hundred fifty seven patients (35.8%) had malnutrition. Patchy infiltrate was found in 80.8% chest X-ray examination. Mortality was found in 4.3%. Conclusions: Community acquired pneumonia in children still count as a major problem at Soetomo Hospital Surabaya.